(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The buffaloes are reared by many races under diverse agro-climatic conditions of Bangladesh. The buffaloes of Bangladesh are mostly indigenous in origin. Both the swamp and river type buffaloes are found in Bangladesh and they can be found throughout the country. However, their concentration is higher in coastal part, Meghna-Ganga and Jamuna-Brahamaputra flood plain, subsequently forming buffalo pockets. This study was conducted to identify the types of buffaloes and the sources of breeding buffaloes in one of those buffalo pockets called Kanihari buffalo pocket situated in Mymenshing district. Direct interviewing method was used to collect the data from the owner of the buffaloes. According to the body shape, coat color and horn pattern, buffaloes of this region were categorized into different categories. Abundant natural green grasses in the river bank of old Brahammaputra gave this area as a shape of a buffalo pocket. This pocket does not have any distinct breed and the buffalo population is mostly mixed and exotic. Introduction of swamp germplasm occurred when buffalo cows are temporarily migrated to Bathan area of Sylhet. Morphometric characteristics (coat color, horn pattern and body appearance) of Type-1, Type-2 and Type-3 buffaloes are similar to Murrah group (Murrah and Nili- Ravi), Surti group and indigenous river type buffaloes, respectively. This is the first study which identifies and morphologically characterizes the buffalo population in Kanihari buffalo pocket; however, in depth genotypic study is required in order to identify the origin or breeds available in this area. Res. Agric., Livest. Fish.2(1): 109-115, April 2015